Dispersive solid phase extraction and quadruple isotope dilution-mass spectrometry combination for the accurate and sensitive quantification of capsaicin in pepper, domestic wastewater and human saliva samples by gc-ms system - Bodur, Süleyman; Erarpat Bodur, Sezin; Gürsoy, Selim; Fırat Ayyıldız, Merve; Kartoğlu, Bedrihan; Akbıyık, Hilal; Bakırdere, Sezgin (My University, 2025)
In the presented study, reduced graphene oxide/Fe3O4 (rGO/Fe3O4) nanocomposites based dispersive solid phase extraction (DSPE) – gas chromatography–mass spectrometry (GC–MS) method was developed for the determination of capsaicin in domestic wastewater (DW), pepper (PP) and human saliva (HS) samples. All important parameters of the DSPE method affected the preconcentration factor were carefully optimized to achieve high signal to noise ratio for the analyte. After the optimization studies, the system analytical performance of DSPE-GC–MS system was evaluated using the aqueous standard solution of capsaicin. Limit of detection (LOD), limit of quantitation (LOQ) and dynamic range were figured out to be 0.54 µg/kg, 1.80 µg/kg and 2.66 – 487.35 µg/kg, respectively. Under the optimum experimental conditions, recovery studies were conducted with the spiked DW, PP and HS samples, and percent recovery results were recorded between 52.6 % and 183.6 % via matrix matching calibration strategy. After the implementation of ID4 strategy, percent recovery results for the spiked DW, PP and HS samples were calculated as 98.2 %–99.3 %, 99.7 %–100.7 % and 99.4 %–99.8 %, respectively. In addition, capsaicin content in Sivri (S)-PP, Kıl (K)-PP and Samandağ (SA)-PP samples were found to be 309.5 ± 11.8 mg/kg, 873.7 ± 26.7 mg/kg and 165.3 ± 5.1 mg/kg via DSPE-GC-ID4-MS method, respectively. As a result, the combination of quadruple isotope dilution (ID4) strategy and the DSPE-GC–MS method were successfully performed to boost the accuracy and precision of developed DSPE-GC–MS method.
Keywords: Capsaicin; Dispersive Solid Phase Extraction; Domestic Wastewater; Pepper; Quadruple Isotope Dilution